Comparing Dominant and Non-Dominant Hand Performance With Force Changes In a Two Hand Equilibrium Task: A Challenge to Dominant Hand Theories - Yaser Khanjari (Biyumikānīk-i varzishī, 2022)
Objective: Although most studies believe that the dominant hand performs better than the non-dominant hand in performing various tasks, there is still the challenge among researchers as to why the non-dominant hand performs better than the dominant hand in certain situations and tasks. The aim of this study was to compare dominant and non-dominant hand performance with force changes in a two-handed balance task. Methods: The samples of this study consisted of 30 male and female subjects with age (y) Mean±SD of 28±6.5. This research was conducted in Shiraz Health Center. In this study, a Huber device was used to measure hand function. Results: The results of the independent t-test showed that when the force on the handle sensor was the same in both hands, the performance of the dominant and non-dominant hand did not differ significantly (P>0.05). However, the dominant hand performed better when the dominant hand-applied more force and the non-dominant hand performed better than the dominant hand when the non-dominant hand applied more force to the handles (P<0.05). Conclusion: The results of this study showed that the performance of the superior hand is not always better than the non-superior hand and the performance of both hands depends on the type of task, synthetic factors (force), and the amount of attention to each hand. These results support the theory of dynamic systems and the specialized hemisphere model in hand control.